Lamb feeding experiments - Menzies, C.S.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
Six hundred and forty mixed wether and ewe fine-wool, feeder lambs were received at the Zuni Indian Reservation near Gallup, N.M., October 18, 1962. They averaged 61.9 pounds at the receiving point and 58.6 pounds off railroad cars at Garden City, three days later.
Keywords: Sheep; Implant; Roughages